Cell-free supernatant of Lactobacillus gasseri 1A-TV shows a promising activity to eradicate carbapenem-resistant Klebsiella pneumoniae colonization - Vertillo Aluisio, Gaia; Mezzatesta, Maria Lina; Cafiso, Viviana; Scuderi, Renata; Stefani, Stefania; Santagati, Maria (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundThe use of beneficial bacteria like Lactobacillus spp. is a potential innovative approach to fight antibiotic-resistant pathogens. Klebsiella pneumoniae is one of the most concerning multi drug-resistant (MDR) pathogens, and its ability to colonize the human gut is considered to be the main reason for recurrent infections in critically ill patients.MethodsIn this study, Lactobacillus gasseri 1A-TV, already described for its probiotic activity, was characterized at the genomic level. Moreover, its cell-free supernatant (CFS) was tested for antimicrobial activity against extended-spectrum β-lactamase (ESBL)- and carbapenemase (KPC)-producing K. pneumoniae clinical isolates.ResultsWhole-genome sequencing showed that the L. gasseri 1A-TV genome was of 2,018,898 bp in size with 34.9% GC content, containing 1,937 putative protein coding sequences, 55 tRNA, and 4 rRNA detected by RAST and classified in 20 functional groups by Cluster of Orthologous Genes (COG). BAGEL4 (BActeriocin GEnome minimal tooL) and the antiSMASH 7.0 pipeline identified two bacteriocin biosynthetic gene clusters (BBGCs), namely, BBGC1 that comprises two class IIc bacteriocins including gassericin A-like bacteriocin, and BBGC2 carrying the class III bacteriocin helveticin J. Strikingly, 1A-TV CFS inhibited the growth of all K. pneumoniae isolates only after 8 h of incubation, showing a bactericidal effect at 24 h and interfering, even at lower concentrations, with the biofilm production of biofilm-producer strains independently of a bactericidal effect. NMR analysis of CFS identified and quantified several metabolites involved in carbohydrate metabolism and amino acid metabolism, and organic acids like ethanol, lactate, acetate, and succinate. Finally, in vitro assays of 1A-TV showed significant co-aggregation effects against carbapenem-resistant K. pneumoniae, namely, strains 1, 2, 3, and 7.ConclusionsOur findings highlight the antimicrobial activity of 1A-TV as a probiotic candidate or its CFS as a natural bioproduct active against MDR K. pneumoniae strains, underlining the importance of novel therapeutic strategies for prevention and control of ESBL- and carbapenemase-producing K. pneumoniae colonization.